PERANCANGAN USER INTERFACE APLIKASI TOKO ONLINE “MORMO STORE” BERBASIS MOBILE APPLICATION - Rahmat Taufiq; dini faisal (DEKAVE : Jurnal Desain Komunikasi Visual, 2020)
The design of the user interface page of the mobile application page of the online shop "Mormo  Store" aims to develop and increase sales of Mormo products online so that it can expand the reach of product marketing places outside the city of Padang. Buyers are also made easy to make product purchases without having to come directly to an offline store, so as to save the time and effort of buyers.The glass box method is a method that thinks logically and rationally used in the user interface design of the mobile application page of the online store "Mormo Store". In the process ofsolving problems using 5W + 1H analysis (what, who, where, when, why, how) to find solutions to the problems encountered. In compiling the flow of interactions with the application an observation is made of the user's behavior and desires, then the results of the study and observations are arranged in a layout that is as simple as possible.The main media produced in this design is the user interface application page online store mormo store. To support the main media, supporting media were created, namely motion graphics, x-banners, plastic bags, label packaging, notebooks, tumblers, and acrylic display stands. In order for the resulting design to have good results, a designfeasibility test was carried out on fifteen samples. Design tests conducted include the appearance, convenience, and comfort of the user in using the application. Based on the feasibility test that has been done, it can be concluded that the user interface of the mormo store online store application page is very well judged from the appearance, ease and comfort of the user in operating the application page.Keywords: mobile application, online store, mormo store, user interface